Inverter-based modeling and energy efficiency analysis of off-grid hybrid power system in distributed generation - AKPOLAT, ALPER NABİ; DURSUN, ERKAN (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Distributed Generation systems are made up of different power generation systems, which are wind turbines, solar panels, fuel cells, energy storage units, micro turbines, and combined heat cycle plants. An inverter is one of the most critical components of Distributed Generation systems. This paper focuses on inverter-based modeling and energy efficiency analysis of the off-grid hybrid system in Distributed Generation. The proposed system is created and simulated using MATLAB/Simulink platform. The obtained results show that the efficiency of the inverter varies between 49.671% and 93.794% under different loads. Model results comply with the inverter efficiency curve specified by the European Commission and U.S. Department of Energy procedures. In the model, the inverter energy efficiency of the hybrid system is compared according to temperature, wind speed, solar radiation, and hydrogen pressure. The inverter exhibits superior performance at low hydrogen pressures. Besides, the efficiency of the inverter is analyzed under load changes.
Keywords: Energy efficiency; Inverter; Hybrid power system; Modeling; Distributed generation